Highly Luminescence Anthracene Derivatives as Promising Materials for OLED Applications. Issue 23 (19th July 2016) - Slodek, Aneta; Filapek, Michal; Schab‐Balcerzak, Ewa; Grucela, Marzena; Kotowicz, Sonia; Janeczek, Henryk; Smolarek, Karolina; Mackowski, Sebastian; Malecki, Jan Grzegorz; Jedrzejowska, Agnieszka; Szafraniec‐Gorol, Grazyna; Chrobok, Anna; et al.
Abstract : Novel symmetrical anthracene derivatives with bulky carbazolyl‐fluorene, diphenylamino‐fluorene, or carbazolyl‐carbazole units connected to the anthracene frame through an ethynyl bridge were synthesized in excellent yield by using Sonogashira cross‐coupling. The ethynyl bridge in the anthracene dyes increases π‐electron conjugation and the bulky substituents considerably attenuate intermolecular interactions. The dyes possess high thermal stability, tremendous solubility in common organic solvents, and especially high photoluminescence quantum yield ( Φ f ) in solution in the range of 77–98 %. OLED devices were fabricated. The AFM images of thin films and blends prepared from all compounds show a uniform and flat surface, indicating excellent film‐forming properties. Devices incorporating the anthracene derivative with diphenylamino‐fluorene end‐capping groups exhibited the highest value of current density ( J ). All of the fabricated OLED devices emitted yellowish‐orange light under applied voltage. Abstract : Symmetrical anthracene derivatives with bulky units connected to the anthracene frame through an ethynyl bridge were synthesized and their electrochemical, photophysical, and electrical properties were characterized. The compounds were yellowish‐orange emitters with high thermal stability, had excellent solubility in most organic solvents, and very high photoluminescence quantum yield in solution.